2013
DOI: 10.1186/1756-9966-32-85
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 SNP309 polymorphism contributes to endometrial cancer susceptibility: evidence from a meta-analysis

Abstract: ObjectiveThe SNP309 polymorphism (T-G) in the promoter of MDM2 gene has been reported to be associated with enhanced MDM2 expression and tumor development. Studies investigating the association between MDM2 SNP309 polymorphism and endometrial cancer risk reported conflicting results. We performed a meta-analysis of all available studies to explore this association.MethodsAll studies published up to August 2013 on the association between MDM2 SNP309 polymorphism and endometrial cancer risk were identified by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…35 In addition, there are several studies showing the effects of MDM2 alteration on endometrial cancer. 36,37 Goumenou et al reported higher MDM2 expression in tissue samples of endometriomas. 38 Also, the relation between MDM2 expression and leiomyosarcomas have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition, there are several studies showing the effects of MDM2 alteration on endometrial cancer. 36,37 Goumenou et al reported higher MDM2 expression in tissue samples of endometriomas. 38 Also, the relation between MDM2 expression and leiomyosarcomas have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that MDM2 overexpression may play a role in development of the subset of leiomyomas and leiomyosarcomas which have different patterns of molecular alterations with separate biologic entities . In addition, there are several studies showing the effects of MDM2 alteration on endometrial cancer . Goumenou et al .…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is one Reproductive outcomes and individual repair capacity of the most common endocrine abnormalities in women of reproductive age and may be a serious risk factor for infertility, as it may interfere with ovulation patterns or altogether preclude ovulation. The variant (G) allele of the MDM2 SNP309 polymorphism (rs2279744) is known to be associated with higher levels of MDM2, resulting, in turn, in lower levels of p53 and, respectively, decreased p53-dependent suppression of cell proliferation [75], which may explain its association with increased risk for endometrial cancer [76]. The association with increased risk for PCOS was identified for the wildtype (T) MDM2 allele [74].…”
Section: Role Of Individual Repair Capacity In the Constitution Of Thmentioning
confidence: 99%
“…If this data set had been included in the meta-analysis, it would weigh approximately 50 % and, therefore, would have had a major impact on the output, both in the overall assessments and even more so in the subgroup of Caucasians. Notably, our data set, in addition to being published in our original article [2], was also included in a previous meta-analysis assessing the impact of SNP309 on endometrial cancer risk [3].…”
Section: Dear Editormentioning
confidence: 99%